Novel Magnetic Properties in Curved Geometries - Bran, Cristina (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint focuses on fundamentals and applied research on magnetic structures with curved geometries. The influence of curvature in the magnetic structures is an appealing topic of research opening novel perspectives to engineer the magnetic textures and the magnetisation reversal processes. Special attention is given to the fabrication and optimisation of magnetic structures, their characterisation and possible use in technological applications.